Risiko Kejadian Abortus pada Ibu Hamil dengan Advanced Maternal Age (AMA) di RSUD Kota Malang - Megawati, Galih; Arifiandi, Maya Devi; Windari, Era Nurisa (Madu Jurnal Ilmu Kebidanan, 2025)
Social changes have led to delayed marriage and pregnancy planning due to higher educational attainment, career demands, and economic considerations. This shift has increased the number of pregnancies among women with Advanced Maternal Age (AMA), which is associated with a higher risk of miscarriage. This study aimed to analyze the risk of miscarriage among pregnant women with Advanced Maternal Age (AMA) at RSUD Kota Malang. This study employed a retrospective case-control design using medical record data. The study population consisted of pregnant women with gestational age <22 weeks during August 2024–July 2025. Purposive sampling was applied to obtain 108 respondents, including 54 cases and 54 controls with a 1:1 ratio. Maternal age was defined as the independent variable, while miscarriage was the dependent variable. Data was analyzed using the chi-square test to determine the association between variables, and odds ratio (OR) with a 95% confidence interval (CI) was calculated. The incidence of miscarriage among women with AMA was 73.7%, compared to 37.1% in women aged 20–34 years. Statistical analysis showed a significant association between AMA and miscarriage (p=0.001). Pregnant women with AMA had a 4.7-fold higher risk of miscarriage (OR=4.738; 95% CI: 1.986–11.307) than those of reproductive age. Advanced Maternal Age significantly increases the risk of miscarriage, indicating the importance of preconception counseling and intensive antenatal monitoring for women of advanced age.